1998
DOI: 10.1089/jir.1998.18.1019
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Sensitive and Selective Bioassay for Human Type I Interferons

Abstract: We describe a novel MxA gene-induction assay for type I interferons (IFN-alpha and IFN-beta) based on the specific induction of the MxA gene in cultured human cells. Accumulated intracellular MxA protein is determined by immunologic measurement by a rapid method using commercially available materials. IFN activity can be measured accurately over a concentration range of 0.1-30 IU/ml. In contrast, type II IFN and other cytokines are not significantly detected. The MxA-induction assay has advantages in terms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…For quantitative detection of human Mx proteins, several enzyme-linked immunosorbent assay (ELISA) formats have been described (10,12,16,53). These procedures are easily adopted to evaluate large sample numbers, yet they depend on two antibodies targeting different epitopes on the same antigen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For quantitative detection of human Mx proteins, several enzyme-linked immunosorbent assay (ELISA) formats have been described (10,12,16,53). These procedures are easily adopted to evaluate large sample numbers, yet they depend on two antibodies targeting different epitopes on the same antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the detection of IFN-␣ or antiviral proteins, namely, Mx proteins, is likely to constitute an indirect approach for investigating the hypothesis of the role of viruses in chronic diseases with suspected infectious etiology (9). In the paraclinical setting it was ultimately recognized that Mx protein was a sensitive and selective substitute to measure an IFN-␣/␤-induced state (16,19,53).…”
mentioning
confidence: 99%
“…NAb measurements were performed using the Myxovirus protein A (MxA) inhibition assay from Berlex Laboratories (Richmond, CA, USA). Details regarding characterization and optimization of the MxA assay used in the study were reported previously [13]. Briefly, all the samples from patients were collected and stored at -20C.…”
Section: Neutralizing Antibodiesmentioning
confidence: 99%
“…The property of IFN-g to act synergistically with type I IFN in the MxA induction in cells has already been applied by Files et al [1998] for detecting neutralizing antibodies to IFN-b1b in sera taken from IFN-b-treated MS patients. For the ®rst time to our knowledge, this property has been used in the current study to investigate the level of endogenous IFN-a in serum from MS patients.…”
Section: Discussionmentioning
confidence: 99%